Institutional Arrangements for Fintech Regulation and Supervision - Taylor, Charles (FinTech Notes; FinTech Notes ;, 2020)
Fintech developments are shaking up mandates within the existing regulatory architecture. It is not uncommon for financial sector agencies to have multiple policy objectives. Most often the policy objectives for these agencies reflect prudential, conduct and financial stability policy objectives. In some cases, financial sector agencies are also allocated responsibility for enhancing competition and innovation. When it comes to fintech, countries differ to some extent in the manner they balance the objectives of promoting the development of fintech and regulating it. Countries see fintech as a means of achieving multiple policy objectives sometimes with lesser or greater degrees of emphasis, such as accelerating development and spurring financial inclusion, while others may support innovation with the objective of promoting competition and efficiency in the provision of financial services. This difference in emphasis may impact institutional structures, including the allocation of staff resources. Conflicts of interest arising from dual roles are sometimes managed through legally established prioritization of objectives or establishment of separate internal reporting lines for supervision and development.